Management of irigation systems in padi growthusesin the context of climate change: Panincong Village Case Kec. Marioriawa Kab. Soppeng - Zahra Maharani; Saediman, Saediman; Munirwan Zani (International Journal of Technology and Education Research, 2024)
This study aims to: (1) determine the impact of climate change on the availability of water for paddy rice farming in Panincong Village, Marioriawa District, Soppeng Regency; (2) determine the perception of farmers related to the management of irrigation systems for paddy rice farming in Panincong Village, Marioriawa District, Soppeng Regency; and (3) determine the perception of farmers related to changes in the management of irrigation systems for paddy rice farming in Panincong Village, Marioriawa District, Soppeng Regency as a result of climate change. This research was conducted from March to July 2024, in Panincong Village, Marioriawa District, Soppeng Regency. The population in this study were owner farmers in Panincong Village who had cultivated rice paddies for at least 15 years, as many as 50 rice paddy farmers. Determination of the sample is done by using a census or saturated sampling technique where all members of the population are used as research samples. Data analysis used is descriptive analysis by combining scoring and qualitative descriptive. The results showed that the impact of climate change on the availability of water for rice paddy farming in Panincong Village includes; water shortages on rice fields, changes in river water discharge and changes in groundwater availability. Farmers' perceptions related to the management of irrigation systems from various aspects are in the medium/good and high/good categories. Farmers' perceptions of irrigation infrastructure are in the high or good category, irrigation water is in the medium or good enough category, irrigation management is in the medium or good enough category, irrigation management institutions are in the high or good category and human resources are in the high or good category. Farmers' perceptions related to changes in the management of irrigation systems in wet-rice farming due to climate change from various aspects are in the category of low / poor and moderate / quite good. Farmers' perceptions of irrigation infrastructure are in the moderate or quite good category, irrigation water is in the low or poor category, irrigation management is in the moderate or quite good category, irrigation management institutions are in the moderate or quite good category and human resources are in the moderate or quite good category.